Hospitality to difference: LGBT, religious education and the Catholic school - Coll, Roisín (Journal of Religious Education, 2021)
There has been a rise in claims of LGBTI youth in schools generally across the UK with a surge in young people self-identifying. This is a ‘theme’ or ‘matter’ or ‘question’ that has been insufficiently ventilated in relation to the Catholic school. It is shrouded in inhibition, confusion, evasion or fear. Burying our heads in the sand is not helping us move forward and there is a potential political threat to the mission of Catholic schools from failing to engage. A key driver of this paper is the rapidly changing climate of opinion and activism around LGBTI experiences in schools and society. From an essentially rights based perspective, and supported by powerful equality legislation, people are campaigning vigorously through formal and informal groups for what they perceive as a redress of longstanding exclusion and discrimination. The concern in particular for LGBTI rights and recognition for under 18s has inevitably drawn schools into these national debates. Three narratives are worthy of discussion around this theme and are inextricably linked: the legal, theological and pastoral narratives. This paper will consider these and suggest the impact that developments are having on the Catholic school sector, and in particular, the teaching of Religious education.